1986
DOI: 10.2337/diab.35.8.894
|View full text |Cite
|
Sign up to set email alerts
|

Are Insulin Autoantibodies Markers for Insulin-Dependent Diabetes Mellitus?

Abstract: Recent studies have shown that insulin autoantibodies occur in patients with newly diagnosed insulin-dependent diabetes mellitus (IDDM) before exogenous insulin treatment. Our study was designed to test the hypothesis that insulin autoantibodies, like cytoplasmic islet cell antibodies (ICAs), can identify individuals with ongoing autoimmune beta-cell destruction and increased risk of IDDM development. Insulin autoantibodies detected by use of a radioligand-binding assay were found in 1.4% of normal controls, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
3

Year Published

1987
1987
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 9 publications
(15 reference statements)
4
51
3
Order By: Relevance
“…It is also noteworthy that despite lower insulin levels during the IVGTT, the relatives of diabetic patients -especially these with positive autoantibodies -had significantly higher fasting insulin concentrations and higher HOMA-IR index than had the controls. Moreover, a positive correlation between IAA levels and HOMA-IR was found in the study group, confirming the previous observations suggesting that not only decreased beta-cell secretory reserve, but also increased insulin resistance, impact upon the progression of the autoimmune process, especially in subjects with auto-antibodies directed against pancreatic islet antigens [17][18][19]. Abnormal sensitivity to insulin in patients with type 1 diabetes was shown for the first time by Ginsberg in the 1970s [20].…”
Section: Prace Oryginalnesupporting
confidence: 88%
“…It is also noteworthy that despite lower insulin levels during the IVGTT, the relatives of diabetic patients -especially these with positive autoantibodies -had significantly higher fasting insulin concentrations and higher HOMA-IR index than had the controls. Moreover, a positive correlation between IAA levels and HOMA-IR was found in the study group, confirming the previous observations suggesting that not only decreased beta-cell secretory reserve, but also increased insulin resistance, impact upon the progression of the autoimmune process, especially in subjects with auto-antibodies directed against pancreatic islet antigens [17][18][19]. Abnormal sensitivity to insulin in patients with type 1 diabetes was shown for the first time by Ginsberg in the 1970s [20].…”
Section: Prace Oryginalnesupporting
confidence: 88%
“…In addition to autoantibodies directed against islet cell proteins (Bottazzo et al, 1980) and glutamic acid decarboxylase (Baekkeskov et al, 1982(Baekkeskov et al, , 1990Kaufman et al, 1992) the IAA are useful in the investigation diagnosis of IDDM (Palmer et al, 1983;Atkinson et al, 1986;Dean et al, 1986;Wilkin, 1990). In newly diagnosed IDDM patients the frequency of IAA is about 40% in children, but only 4% in adults (Karjalainen et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-insulin autoantibodies (IAAs) were the first specific ICAs to be identified and this was done in 1983 by Palmer et al [27] who performed seminal studies in this area using serum from patients who have not been challenged by exogenous insulin at the time of sample collection. Subsequent research have addressed the insulin levels after glucose challenge and it was concluded that insulinopenia was more prevalent in subjects possessing both, ICAs and IAAs, compared to those being positive just for ICAs [28] . However, this marker has a relatively low sensitivity, being even less than 40% [29] .…”
Section: Immunological Characteristicsmentioning
confidence: 99%